2022
DOI: 10.3390/ijerph19063673
|View full text |Cite
|
Sign up to set email alerts
|

The Problematic Role of Materialistic Values in the Pursuit of Sustainable Well-Being

Abstract: Strong materialistic values help to maintain consumer capitalism, but they can have negative consequences for individual well-being, for social equity and for environmental sustainability. In this paper, we add to the existing literature on the adverse consequences of materialistic values by highlighting their negative association with engagement in attitudes and actions that support the achievement of sustainable well-being. To do this, we explore the links between materialistic values and attitudes towards s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 91 publications
(134 reference statements)
3
17
0
Order By: Relevance
“…Work conducted so far has documented a negative association between materialism and flow experiences . Results from Isham et al (2021a;2021b) and demonstrated, using cross-sectional surveys, that those individuals reporting stronger materialistic goals and values also tended to be less flow prone. That is, materialistic individuals are less likely to experience the characteristics of flow in their day-to-day lives.…”
Section: Materialistic Goal Orientation and Flow In Environmental Psy...mentioning
confidence: 98%
See 3 more Smart Citations
“…Work conducted so far has documented a negative association between materialism and flow experiences . Results from Isham et al (2021a;2021b) and demonstrated, using cross-sectional surveys, that those individuals reporting stronger materialistic goals and values also tended to be less flow prone. That is, materialistic individuals are less likely to experience the characteristics of flow in their day-to-day lives.…”
Section: Materialistic Goal Orientation and Flow In Environmental Psy...mentioning
confidence: 98%
“…Whilst the negative effect of materialistic goals on flow experiences has been demonstrated in previous work, studies are only beginning to try to understand why strong materialistic goals may have their flow-limiting effects. Isham et al (2021b) explored the potential role of self-regulationwhich refers to each individual's ability to manage their own thoughts, emotions and behavioursin explaining this negative relationship. They found that more materialistic individuals tended to have lower trait levels of self-regulatory strength which, in turn, was linked to a lesser tendency to experience flow in their daily lives.…”
Section: Theory Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the main goal of campus discussion and advocacy will need to be convincing campus administrators to move beyond neoliberal logic and implement the campus public-good mission in the food environment. Therefore, acknowledgement of and “systematic engagement” with the neoliberal assumptions [ 71 , 72 ] driving PHEI business policies is needed, including the moral values embedded in those assumptions [ 69 , 115 , 119 ], followed by discussion of how to prioritize public-good values and policies that respond adequately to the public and planetary health crisis, e.g., degrowth instead of economic growth, ecological economics instead of neoclassical economics, and sufficiency instead of superfluous consumption [ 15 , 112 , 120 ].…”
Section: How Can Pheis Transform Campus Food Environments Commensurat...mentioning
confidence: 99%